How Do South American International Students Experience Student Life in Flanders? A Photo Elicitation Project - Wang, Qingchun; Leen, Steffanie; Hannes, Karin (Journal of International Students, 2018)
Millions of tertiary international students are studying abroad, and the number of exchange students continues to increase. We explored experiences of South American students studying in a non-Anglophone context. A photo elicitation methodology was applied to support data collection. Five participants were asked to visualize their challenges in their adjustment in pictures. We conducted individual interviews where images were used as prompts to narratives. Data were analyzed using a thematic analysis approach. Three main themes were identified: socio-cultural adjustment, academic adjustment, and psychological adjustment. Our data suggest that adjustment processes do not automatically lead to an adaptation outcome. Individual factors such as students’ acculturation strategies and coping mechanisms, and situational variables like social interaction and cultural discomfort affect their adjustment.